A Safer Prescription: Quality Improvement in Medication Practices on West Ward - Mehtab Rahman; Ghazi Seekolu Jhansi; Somya Pandey; Shainy Christopher (BJPsych Open, 2025)
Aims: To reduce medication errors on West Ward, a busy adult mental health ward, by addressing multiple domains of medication safety identified in a baseline audit. The project aimed to improve prescribing practices, medication administration, and related processes through targeted interventions and continuous monitoring.